Phase I Study of Cetuximab, Irinotecan, and Vandetanib (ZD6474) as Therapy for Patients with Previously Treated Metastastic Colorectal Cancer - Meyerhardt, Jeffrey A.; Ancukiewicz, Marek; Abrams, Thomas A.; Schrag, Deborah; Enzinger, Peter C.; Chan, Jennifer A.; Kulke, Matthew H.; Wolpin, Brian M.; Goldstein, Michael; Blaszkowsky, Lawrence; Zhu, Andrew X.; Elliott, Meaghan; et al. (PLOS ONE, 2012)
Background To determine the maximum tolerated dose (MTD) and safety, and explore efficacy and biomarkers of vandetanib with cetuximab and irinotecan in second-line metastatic colorectal cancer. Methods Vandetanib (an orally bioavailable VEGFR-2 and EGFR tyrosine kinases inhibitor) was combined at 100 mg, 200 mg, or 300 mg daily with standard dosed cetuximab and irinotecan (3+3 dose-escalation design). Ten patients were treated at the MTD and plasma angiogenesis biomarkers (VEGF, PlGF, bFGF, sVEGFR1, sVEGFR2, IL-1β, IL-6, IL-8, TNF-α, SDF1α) were measured before and after treatment. Results Twenty-seven patients were enrolled at 4 dose levels and the MTD. Two dose-limiting toxicities (grade 3 QTc prolongation and diarrhea) were detected at 300 mg of vandetanib with cetuximab and irinotecan resulting in 200 mg being the MTD. Seven percent of patients had a partial response, 59% stable disease and 34% progressed. Median progression-free survival was 3.6 months (95% CI, 3.2–5.6) and median overall survival was 10.5 months (95% CI, 5.1–20.7). Toxicities were fairly manageable with grade 3 or 4 diarrhea being most prominent (30%). Vandetanib and cetuximab treatment induced a sustained increase in plasma PlGF and a transient decrease in plasma sVEGFR1, but no changes in plasma VEGF and sVEGFR2. Conclusions Vandetanib can be safely combined with cetuximab and irinotecan for metastatic colorectal cancer. Exploratory biomarker analyses suggest differential effects on certain plasma biomarkers for VEGFR inhibition when combined with EGFR blockade and a potential correlation between baseline sVEGFR1 and response. However, while the primary endpoint was safety, the observed efficacy raises concern for moving forward with this combination. Trial Registration Clinicaltrials.gov NCT00436072.